Co-occurring Mental Disorders in Transitional Aged Youth With Substance Use Disorders – A Narrative Review - Köck, Patrick; Meyer, Maximilian; Elsner, Julie; Dürsteler, Kenneth M.; Vogel, Marc; Walter, Marc (Frontiers in Psychiatry, 2022)
Adolescence and emerging adulthood are often referred to as youth. Transitional psychiatry addresses this target group, which considers patients between 15 and 25 years of age. Substance use usually begins and peaks at this stage of life. Psychiatric disorders, foremost attention-deficit/hyperactivity disorder, and affective disorders, conduct disorders, and first-episodes psychosis frequently appear in early life stages. This review aims to provide a broad overview of transitional-aged youth's most common psychiatric comorbidities with substance use disorders. A literature search was conducted in Embase and Pubmed, and the main findings are described narratively. We present main findings for the following comorbidities: attention-deficit/hyperactivity disorder, conduct disorder, personality disorders, affective disorders, psychotic disorders, and the phenomena of overdose and suicidality. In conclusion, co-occurring mental health disorders are common and appear to facilitate the development of substance use disorders and exacerbate their overall course. Substance use also affects the severity and course of comorbid psychiatric disorders. Overall, data on transition-age youth with substance use disorders are highly inconsistent. Universal screening and treatment guidelines do not yet exist but should be aimed for in the future.